2017
DOI: 10.1121/1.5005508
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of psychoacoustic-based reverberance parameters

Abstract: This study compared psychoacoustic reverberance parameters to each other, as well as to reverberation time (RT) and early decay time (EDT) under various acoustic conditions. The psychoacoustic parameters were loudness-based RT (T), loudness-based EDT [EDT; Lee, Cabrera, and Martens, J. Acoust. Soc. Am. 131, 1194-1205 (2012a)], and parameter for reverberance [P; van Dorp Schuitman, de Vries, and Lindau., J. Acoust. Soc. Am. 133, 1572-1585 (2013)]. For the comparisons, a wide range of sound pressure levels (SPLs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…these aspects requires further experimental data collection. In a broader context, this paper showed that perception-based predictions of a room acoustic indicator, in this case of reverberance (see also Lee et al, 2017), can be correlated with actual listening experiences in a room that depend on both "sound source" and "receiver." This is in contrast to established measurement guidelines (ISO 3382-1, 2009), where the acoustic properties of a room are considered as linear and time invariant, that is, room properties are assumed to be independent of the type of excitation, and of the level of the exciting signals.…”
Section: Discussionmentioning
confidence: 95%
“…these aspects requires further experimental data collection. In a broader context, this paper showed that perception-based predictions of a room acoustic indicator, in this case of reverberance (see also Lee et al, 2017), can be correlated with actual listening experiences in a room that depend on both "sound source" and "receiver." This is in contrast to established measurement guidelines (ISO 3382-1, 2009), where the acoustic properties of a room are considered as linear and time invariant, that is, room properties are assumed to be independent of the type of excitation, and of the level of the exciting signals.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, if the sized of the room is large and the sound source power is weak, it is advisable to achieve a higher RT to keep the sound audible at all points in the room. As can be observed, the choice of a suitable RT for a given enclosure depends on the final use of the room and the commitment/criterion to be reached in the design stages [9].…”
Section: Reverberation Time (Rt) For the Assessment Of Acoustic Room ...mentioning
confidence: 99%
“…In this sense, an appropriate acoustic behaviour for a given indoor space should be already guaranteed from the early design phase, working with some potential available objective parameters to allow evaluating the acoustic characteristics of a room [6][7][8]. Among these parameters this work focus in the reverberation time, denoted as RT, which is certainly one of the most important variables or physical factors considered by experts in the design of interior spaces [9]. In fact, the RT is used as the key parameter in the acoustic assessment of enclosures.…”
Section: Introductionmentioning
confidence: 99%
“…An issue here is that listening to a BRIR is different from listening to anechoic samples convolved with the same BRIR. Nevertheless, in previous studies (Lee et al, 2012;Lee et al, 2017), the reverberation parameters calculated from the loudness decay of a RIR outperformed significantly the conventional reverberation time and early decay time for various anechoic samples convolved with the same RIR. This is because the perceived decay of a RIR is a good match to the overall perceived reverberation decay of the convolution products (as a RIR is the only source of the reverberation of the convolution products).…”
mentioning
confidence: 90%